P07.09 A validation study of the cepheid xpertâ ct/ng for detecting chlamydia trachomatis and neisseria gonorrhoeae in rectal samples. (13th September 2015) - Cosentino, LA; Danby, CS; Rabe, LK; Priest, CL; Damare, KC; Macio, IS; Meyn, LA; Wiesenfeld, HC; Hillier, SL
Abstract : Introduction: The objective of this study was to compare the Cepheid Xpert CT/NG (Xpert) and Gen-Probe Aptima (AC2) systems for the identification of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) from rectal swabs. Methods: Anorectal swabs were collected from 399 participants (224 men and 175 women) who reported a lifetime history of anal receptive intercourse. True positives for this study were defined if both AC2 and Xpert were positive, or if either AC2 or Xpert were positive and the APTIMA CT or APTIMA GC, which target alternate primers, were positive. Results: There was a high level of agreement between Xpert and AC2 for detection of CT and GC from rectal swabs, with only 2/30 discrepant results for GC and 9/59 discrepant results for CT. Following resolution of discrepants, rectal swabs were positive for CT in 58 (14.5%) and for GC in 30 (7.5%) of the 399 participants. For CT, the sensitivity and specificity of Xpert (96.6%, 99.7%) and AC2 (91.4%, 100%) were comparable, with men and women both having high frequencies of rectal CT (17.4% vs 10.9%, P = 0.08). For GC, the sensitivity and specificity of Xpert (100%, 100%) and AC2 (93.3%, 100%) were similar. However, rectal GC was detected much more frequently in men than in women (11.6% vs 2.3%, P < 0.001). Conclusion: Rectal GC and CT were common among people reporting a history of receptive anal sex. Xpert and AC2 had high levels of agreement for rectal swab samples. Disclosure of interest statement: Reagents for CT/GC testing were provided for by Cepheid and Hologic.